X‐ray sterilization of biopharmaceutical manufacturing equipment—Extractables profile of a film material and copolyester Tritan™ compared to gamma irradiation. (3rd October 2021) - Menzel, Roberto; Dorey, Samuel; Maier, Tanja; Pahl, Ina; Hauk, Armin
Abstract: The biopharmaceutical industry gains enormous flexibility in production processes by using sterilized preassembled single‐use devices. Gamma irradiation is an established sterilization technology that may be restricted in the future by the availability of 60 Co as irradiation source and irradiation capacities. X‐ray technology is considered an alternative type of radiation for sterilizing SU equipment. In the context of extractables and leachables—one concern connected with the use of single‐use process equipment—the effect of X‐ray irradiation on the extractables profile of the materials needs to be compared to established gamma irradiation to qualify this alternative technology. An approach is presented to obtain robust and comprehensive extractables data for materials used in SU devices after sterilization either using X‐ray or gamma irradiation. A careful selection of the test items and the test design allows a one‐to‐one comparison of data obtained from a combination of orthogonal analytical techniques. The extractables of a modern SU film material and the copolyester Tritan™ are evaluated. The data presented allow a risk evaluation on the safety of this new sterilization modality for biopharmaceutical applications. It is demonstrated that the extractables profile of a polymer is not affected by the type of irradiation used for sterilization.